Assessing the State of Demersal Fish to Address Formal Ecosystem Based Management Needs: Making Fisheries Independent Trawl Survey Data ‘Fit for Purpose’ - Moriarty, Meadhbh; Greenstreet, Simon P. R.; Rasmussen, Jens; de Boois, Ingeborg (Frontiers in Marine Science, 2019)
In Europe, introduction of the Marine Strategy Framework Directive (MSFD) represents formal, legally-binding, adoption of ecosystem-based management (EBM) across most European waters. Member States of the European Union have invariably nominated their groundfish surveys as part of the marine monitoring programmes required under the MSFD. Groundfish surveys were originally intended to provide fisheries independent abundance indices for commercially valuable species to support fisheries stock assessments and fisheries management. However, early studies, primarily intended to make the case for the need for EBM, exposed these data to a broader range of uses and highlighted various data quality issues. Individual scientists, pursuing personal research agendas, addressed these as each thought best. This informal approach to assuring data quality is not sufficient to support formal assessments of fish species status and fish community status required under legally-mandated EBM, such as the MSFD, because quality audit, formal logging of issues identified, and remedial measures taken, is often lacking. Groundfish survey data, needed to implement legally-mandated EBM, should be subjected to a formal Quality Assurance–Quality Audit (QAQA) process to ensure that they are properly fit for purpose. This paper describes a QAQA process applied European groundfish survey data to ensure their adequacy to support MSFD needs and considers how this process might be taken forward in the future.